Exergy analysis for a proposed binary geothermal power plant in Nisyros Island, Greece. (November 2017) - Koroneos, Christopher; Polyzakis, Apostolos; Xydis, George; Stylos, Nikolaos; Nanaki, Evanthia
Highlights: An experimental geothermal drill in the Greek Island of Nisyros is examined. Data used in order to estimate the maximum available work and the efficiency of a potential power plant. Exergy analysis is performed. Exergy efficiency of 41% and a thermal of 12.8% are calculated supporting technical feasibility of the proposed geothermal plant. Abstract: The exergy analysis method constitutes an alternative but very important technique for the evaluation of the utilization level of thermal plants as well for the comparison of different conversion processes. The loss of exergy provides a figure of merit for the inefficiencies of a process and a measure of the quality of the different forms of energy in relation to given environmental conditions. In this paper, data from an experimental geothermal drill in the Greek Island of Nisyros, located in the south of the Aegean Sea, have been used in order to estimate the maximum available work and the efficiency of a potential power plant. Different methods for estimating the exergy term are used and several types of conversion efficiencies have been calculated in order to obtain a more complemented view of the analysis. Overall, a system exergetic efficiency of 41% and a thermal one of 12.8% have been resulted supporting technical feasibility of the proposed geothermal plant.